Implications of Constitutional Defiance of Constitutional Court Decisions by Lawmakers - Pratiwi, Wiwit; Isra, Saldi; Simabura, Charles; Fahmi, Khairul (Magister of Law, Faculty of Law, University of Mataram, 2025)
Law Examination, when associated in the context of upholding the supremacy of the constitution, does not only stop at canceling a norm of law that is contrary to the constitution, but also how the cancellation decision is then obeyed and implemented. This is because the nature of the Constitutional Court Decision is final and binding. The problem that then arises is when looking at the final and binding nature of the Constitutional Court Decision from the aspect of law in action. It is still found that the Constitutional Court’s decision is not implemented consequently by the legislators, namely by reviving the norms that the Constitutional Court has annulled in the laws to be formed or new laws. The research method used is a normative legal method, which is carried out by collecting primary, secondary, and or tertiary legal materials. The results of the study show that the final and binding nature of Constitutional Court decisions erga omnes requires all state institutions to consider the annulled norms as invalid and to follow up on them without exception. However, the study found that constitutional defiance still occurs in the form of disregard or revival of norms that have been declared unconstitutional, which triggers legal uncertainty and weakens the authority of the constitution. Therefore, stronger implementation mechanisms are needed, including post-decision compliance, constitutional impact assessment, continuous monitoring, and the application of a judicial preview model to ensure the effectiveness of Constitutional Court decisions.